2017
DOI: 10.1186/s12974-017-0905-7
|View full text |Cite
|
Sign up to set email alerts
|

The Carbon monoxide releasing molecule ALF-186 mediates anti-inflammatory and neuroprotective effects via the soluble guanylate cyclase ß1 in rats’ retinal ganglion cells after ischemia and reperfusion injury

Abstract: BackgroundThe endogenously produced gaseous molecule carbon monoxide is able to promote organ protection after ischemia-reperfusion injuries (IRI). The impact of carbon monoxide releasing molecules (CORM) regarding inflammation in neuronal tissues has not been studied in detail. In this investigation, we aimed to analyze the effects of the CORM ALF-186 on neuro-inflammation and hypothesized that the soluble guanylate cyclase (sGC) is playing a decisive role.MethodsRetinal ischemia-reperfusion injury was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…In the first part of this study, we demonstrated that even topical CORM injection into the vitreous body leads to sustained neuroprotective effects in the context of retinal IRI, which has not yet been shown. As recently detected with intravenous application of ALF-186 after IRI [ 17 , 21 ], intravitreal ALF-186 spreads its effects on ischemic RGC in a comparable way and effective power. Intravitreal injection of ALF-186 immediately after reperfusion reduced the extent of RGC loss, corresponding to higher RGC density.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…In the first part of this study, we demonstrated that even topical CORM injection into the vitreous body leads to sustained neuroprotective effects in the context of retinal IRI, which has not yet been shown. As recently detected with intravenous application of ALF-186 after IRI [ 17 , 21 ], intravitreal ALF-186 spreads its effects on ischemic RGC in a comparable way and effective power. Intravitreal injection of ALF-186 immediately after reperfusion reduced the extent of RGC loss, corresponding to higher RGC density.…”
Section: Discussionmentioning
confidence: 66%
“…Intracellular signaling after IRI+ALF intravitreally likewise involved the gene suppression of NF-κB and TNF-α as well as the induction of p38 and HSP 90, as previously described and discussed in detail after intravenous ALF application [ 17 , 21 ]. In both studies, corresponding changes on the level of protein were displayed; we thus decided not to confirm our mRNA results reported here by western blots, although the later would be methodically more valuable.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Intravitreal injection of CORM ALF-186 significantly upregulated GAP43 mRNA expression and RGC regeneration in rat ischemic/reperfusion vascular injury [22]. Moreover, ALF-186 also exerts neuroprotective effects by reducing the expression of inflammatory mediators, such as nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), tumor necrosis factor-α (TNF-α) and IL-6 via the soluble guanylate cyclase β1 in rat RGCs after ischemic/reperfusion vascular injury [69]. In this ischemic model, ALF-186 upregulates Hsp90 mRNA and protein levels [69], possibly affecting the intrinsic mechanism of axon regeneration.…”
Section: Effects Of Co On Neuronal Intrinsic Mechanismsmentioning
confidence: 99%